2007
DOI: 10.1194/jlr.d700006-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Specific and rapid analysis of ubiquinones using Craven's reaction and HPLC with postcolumn derivatization

Abstract: A new method for the analysis of ubiquinones in various samples was developed using an HPLC system with postcolumn derivatization. Craven's reaction, a specific color reaction for the analysis of ubiquinones, was used in the system. Because the reaction progressed in organic solvents that contained ubiquinones and ethylcyanoacetate under an alkaline condition, the selectivity for ubiquinone detection was higher than that for ubiquinone detection using the nonderivatized ultraviolet detection system at 275 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…To the 30 mg wet pellet of the E. tenella sporozoites, 600 μL of 2-propanol was added to extract quinones and quinols. To the 600 μL of supernatant, 6 μL of 2-propanol supplemented with 120 mM FeCl 3 was added to oxidize all the quinol to the quinone [23]. After the removal of insoluble debris by filtration through a 0.2 μm pore-size filter (Ultra-free, millipore), 4 μL of the filtrated extracts was injected to the LC-MS system, consisting of a pump (L-2100, Hitachi, Japan), column oven at 40 °C (L-2300, Hitachi), analytical column (Inertsil ODS-3, 2 μm, 2.1 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…To the 30 mg wet pellet of the E. tenella sporozoites, 600 μL of 2-propanol was added to extract quinones and quinols. To the 600 μL of supernatant, 6 μL of 2-propanol supplemented with 120 mM FeCl 3 was added to oxidize all the quinol to the quinone [23]. After the removal of insoluble debris by filtration through a 0.2 μm pore-size filter (Ultra-free, millipore), 4 μL of the filtrated extracts was injected to the LC-MS system, consisting of a pump (L-2100, Hitachi, Japan), column oven at 40 °C (L-2300, Hitachi), analytical column (Inertsil ODS-3, 2 μm, 2.1 mm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…Cells incubated under anaerobic conditions for 24 h were harvested by centrifugation, and 2‐propanol was added (20 μL·mg −1 wet weight of cells) to extract quinones and quinols. In total, 1 μL of 120 m m FeCl 3 solution dissolved in 2‐propanol was added to 100 μL of the extract to oxidize quinols prior to analysis , and this was used as a sample for measurement. Rhodoquinone‐9 (RQ 9 ) was prepared from Ascaris suum and was used as a standard for HPLC analysis in addition to ubiquinone‐10 (UQ 10 ), which was purchased from Wako Chemicals (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29] Moreover, Craven's reaction gives fluorescent products at a later stage of the reaction. It was reported that ubiquinone incubated at room temperature for 12-24 h in ethyl cyanoacetate with methanolic potassium hydroxide solution resulted in fluorescent products with excitation at 430 nm and emission at 530 nm.…”
Section: Resultsmentioning
confidence: 99%